INNOVATIVE APPROACHES TO LITERARY TRANSLATION IN THE DIGITAL ERA - Bahodir A. Abdirasulov; Aizhan B. Nabiyeva (International Journal of Literature and Language Studies, 2026)
Abstract. The development of digital technologies and the increasing interaction among cultures have transformed modern literary translation. Modern translators are expected not only to transfer linguistic meaning but also to keep the cultural, artistic, and emotional features of literary works. This article discusses innovative methods in literary translation through functional and linguocultural frameworks while highlighting the growing impact of digital tools on the translation process. The study employs descriptive, comparative, and analytical methods to investigate the application of modern translation approaches in literary texts. The findings demonstrate that successful literary translation requires a balance between linguistic equivalence, cultural adaptation, and technological support. The results suggest that effective translation depends on the balanced use of functionalist principles, cultural analysis, and modern digital technologies.